Effects of oil spill response technologies on marine microorganisms in the high Arctic. (October 2019) - Pančić, Marina; Köhler, Eva; Paulsen, Maria Lund; Toxværd, Kirstine; Lacroix, Camille; Le Floch, Stéphane; Hjorth, Morten; Nielsen, Torkel Gissel
Abstract: We studied how exposure to oil spill response technologies affect marine microorganisms during Arctic winter and spring. Microorganisms were exposed to chemically dispersed oil (DISP), in situ burnt oil (ISB), and natural attenuated oil (NATT) in mesocosms from February to May. We subsampled the mesocosms and studied the effects of oil in laboratory incubations as changes in biomass of the major functional groups: bacteria, heterotrophic-nanoflagellates, dinoflagellates, ciliates, pico- and nanophytoplankton, and diatoms over two 14-day periods. In winter, the majority of polycyclic aromatic hydrocarbons (PAHs) remained encapsulated in the ice, and the low concentrations of PAHs in water led to minute changes in biomass of the investigated groups. In spring, however, when the PAHs were partially released from the melting ice, the biomass of many functional groups in DISP and NATT decreased significantly, while the changes in ISB were less pronounced. The overall biomass reduction, as observed in this study, could lead to a disrupted transfer of energy from the primary producers to the higher trophic levels in oil affected areas. Highlights: Oil remediation tools enhance growth of bacteria and heterotrophic nanoflagellates. In situ burning has the least harmful effects on microbial community structure. Chemical dispersant and oil weathering reduce microbial community biomass by 50%.